Fabrication and Evaluation of Selective Membrane Electrodes for the Potentiometric Determination of Diclofenac Sodium in Pure and Pharmaceutical Forms - Faleh, Othman Rafat; Hanoon , Imad Tarek (American Journal of Bioscience and Clinical Integrity, 2025)
This study presents a potentiometric method for determining diclofenac sodium (DIC) through the development of selective membrane electrodes. These electrodes were fabricated using a diclofenac–phosphotungstic acid (PTA) ion-pair complex as the active material, tributyl phthalate (TBPH) as the plasticizer, and polyvinyl chloride (PVC) as the polymer matrix. The fabricated DIC–PTA–TBPH electrode exhibited a near-Nernstian slope of 58.6 mV/decade over a pH range of 3 to 4. It showed a linear response within the concentration range of 1×10⁻⁵ to 1×10⁻¹ M, with a detection limit of 0.02918 M, a response time of 5–35 seconds, and a lifespan of approximately 40 days. The electrode demostratet excellent selectivity for diclofenac ions in the presence of various mono- and divalent interfering ions, with all selectivity coefficient values (K_pot) below 1. The method was successfully applied to the analysis of diclofenac sodium in pharmaceutical tablets, yielded recovery percentages ranging from 90% to 103.5%, comparable to results obtained by HPLC.